The Effect of garlic meal as prebiotic on the growth and survival of young common carp Cyprinus carpio cultivated in earthen ponds - Taher , Majid; Salih , Osamah; Muhammed, Sadiq; Al-Dubakel, Adel; Mojer, Ahmed (Mesopotamian Journal of Marine Sciences, 2024)
The current experiment was conducted in eight earthen ponds (600 m2), and each pond stocked with 1500 young common carp at average weight of 13.2 g. The experiment conducted to investigate the differences in survival rate and growth performance for these young fishes fed diets with different ratio of dried garlic meal as additives [without additives (C), addition of 0.5% garlic (T1), addition of 1% garlic (T2), addition of 1.5% garlic (T3)]. Results of current experiment revealed that highest survival rate (97.8%) was achieved by fish in C and lowest (96.0%) was achieved by fish in T3, while highest daily growth rate (0.3744 g/day) was achieved by fish in T3 and lowest (0.3320 g/day) was achieved by fish in T2. Feed conversions of all treatment were 2.74, 2.85, 2.82 and 2.38 for C, T1, T2 and T3 respectively. Statistical analysis of the results for survival rate, fe141ed conversion rate and all growth criteria studied in current experiment proved that there were no significant differences (P>0.05) between control and other three treatments and also between these treatments. The growth pattern for young common carp before the experiment was negative allometric were b value was 2.6496, while it was positive allometric for all treatments after experiment. There were no significant differences (P>0.05) in relative condition factor between before and after the experiment and also between all treatments